The Curiosity Effect with Barnum Effect on the Tendency of Tarot Divination Addiction in Tarot Lovers in Semarang - Astuti, Puji; Virgonita, Mulya (Sahabat Publikasi, 2024)
This research aims to test and analyze the influence of curiosity and the Barnum effect on the tendency of tarot prediction addiction among tarot lovers in Semarng . This research is a correlational research carried out in Semarang from November 2023 to April 2024. The population of this research is tarot divination lovers in Semarang, where the population size is unknown with 92 research subjects. Samples were taken using snowball sampling technique. Data was collected by questionnaire. The dependent variable in this research is the tendency to get addicted to tarot predictions, while the independent variable is curiosity. Data analysis was carried out with SmartPLS 4.The results of the research show that (1) there is an insignificant influence of curiosity on the tendency to become addicted to tarot divination; (2) there is no significant influence of the Barnum effect on the tendency to become addicted to tarot predictions; (3) there is a significant influence of curiosity on the Barnum effect; (4) there is an insignificant influence of curiosity on the tendency to become addicted to tarot divination through the Barnum effect. The influence/contribution of the curiosity variables , Barnum effect on the tendency to become addicted to tarot predictions is 73%, while the other 26.2% is influenced by other variables outside this research